Decoding Klebsiella pneumoniae in poultry chain: unveiling genetic landscape, antibiotic resistance, and biocide tolerance in non-clinical reservoirs - Mourão, Joana; Magalhães, Mafalda; Ribeiro-Almeida, Marisa; Rebelo, Andreia; Novais, Carla; Peixe, Luísa; Novais, Ângela; Antunes, Patrícia (Frontiers in Microbiology, 2024)
The rise of antibiotic resistance in the food chain is influenced by the use of antimicrobial agents, like antibiotics, metals, and biocides, throughout the entire farm-to-fork continuum. Besides, nonclinical reservoirs potentially contribute to the transmission of critical pathogens such as multidrugresistant (MDR) Klebsiella pneumoniae. However, limited knowledge exists about the population structure and genomic diversity of K. pneumoniae circulating in conventional poultry production. We conducted a comprehensive characterization of K. pneumoniae across the whole chicken production chain (7 farms; 14 flocks+/environment+/meat, 56 samples; 2019-2022), exploring factors beyond antibiotics, like copper and quaternary ammonium compounds (QACs). Clonal diversity and adaptive features of K. pneumoniae were characterized through cultural, molecular (FT-IR), and whole-genomesequencing (WGS) approaches. All except one flock were positive for K. pneumoniae with a significant increase (p<0.05) from early (n=1/14) to pre-slaughter (n=11/14) stages, most persisting in chicken meat batches. Colistin-resistant K. pneumoniae rates were low (4%-n=1/24 positive samples), while most samples carried MDR strains (67%-n=16/24) and copper-tolerant isolates (63%-n=15/24, with; sil and +pco gene clusters; MICCuSO4≥16mM), particularly at pre-slaughter. Benzalkonium chloride consistently exhibited activity in K. pneumoniae (MIC/MBC range=4-64mg/L) from diverse and representative strains independently of the presence or /absence of genes linked to QACs tolerance. A polyclonal K. pneumoniae population, discriminated by FT-IR and WGS, included various lineages dispersed throughout the chicken's lifecycle at the farm (ST29-KL124, ST11-KL106, ST15-KL19, ST1228-KL38), until the meat (ST1-KL19, ST11-KL111, ST6405-KL109, and ST6406-CG147-KL111), or over years (ST631-49 KL109, ST6651-KL107, ST6406-CG147-KL111). Notably, some lineages were identical to those from human clinical isolates. WGS also revealed F-type multireplicon plasmids carrying sil+pco (copper) co-located with qacEΔ1±qacF (QACs) and antibiotic resistance genes like those disseminated in humans. In conclusion, chicken farms and their derived meat are significant reservoirs for diverse K. pneumoniae clones enriched in antibiotic resistance and metal tolerance genes, some exhibiting genetic similarities with human clinical strains. Further research is imperative to unravel the factors influencing K. pneumoniae persistence and dissemination within poultry production, contributing to improved food safety risk management. This study underscores the significance of understanding the interplay between antimicrobial control strategies and non-clinical sources to effectively address the spread of antimicrobial resistance.